MYTHOS AND ADAPTATION: THE RĀMĀYAṆA'S JOURNEY TO THE RAMAKIEN - Fiza Chandiwala (Samā Jiva Jnānam (International Journal of Social Studies), 2025)
A timeless Indian epic, the Rāmāyaṇa evolved into diverse localised forms throughout Southeast Asia, transcending cultural and geographic boundaries. The Ramakien of Thailand stands out among them as a striking example of the epic's versatility and timeless appeal. The primary focus of this study, "Mythos and Adaptation: The Rāmāyaṇa's Journey to the Ramakien," explores the gradual alterations that occurred as the Rāmāyaṇa transitioned from its Indian roots to its Thai version. This study aims to shed light on how the Rāmāyaṇa was amended to reflect Thai customs while retaining its key concepts by analysing the narrative, thematic, and character transformations. The research emphasises how the Ramakien's unique identity was influenced by Thai social, spiritual, and creative abilities. For example, the character Rama in the Ramakien represents Buddhist ideas, unlike his representation in the Rāmāyaṇa. The roles of well-known characters like Sita and Hanuman are also altered, giving the well-known story new depth. Using a comparative literary study, this research highlights how the Ramakien serves as a development and reimagination of the Rāmāyaṇa. The study illustrates how, within the vast global network of cultural transmission, masterpieces like the Rāmāyaṇa evolve as they traverse national boundaries. This paper also demonstrates how inventive civilisations may recreate universal ideas for cultural continuity and change to coexist.